If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 = -6(1 + -4x) 90 = (1 * -6 + -4x * -6) 90 = (-6 + 24x) Solving 90 = -6 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. 90 + -24x = -6 + 24x + -24x Combine like terms: 24x + -24x = 0 90 + -24x = -6 + 0 90 + -24x = -6 Add '-90' to each side of the equation. 90 + -90 + -24x = -6 + -90 Combine like terms: 90 + -90 = 0 0 + -24x = -6 + -90 -24x = -6 + -90 Combine like terms: -6 + -90 = -96 -24x = -96 Divide each side by '-24'. x = 4 Simplifying x = 4
| x/7-7/4=x/14-1/28 | | 3(4t-8)+3=6 | | 560=x+x+3x-90 | | -8x+7+10x=4 | | 12(x+5)=2(10+3) | | (c+.5)(c+.5)= | | 2b-5-7b-3= | | 18x-6x+2x=0 | | (w-4/9)(2/3)=-4/3 | | 4x+6-x=12 | | 10/3.69=12/x | | (8-18y)-(15+2y)= | | 6x-5=4x+8 | | 0.8x+6=7.2 | | 3a+4=a-18 | | 20/12=12/5 | | 22=2x+6x-10 | | Lx+My=N | | 6=(x/9.6) | | 3x+3=-34 | | Lx+My=Nfory | | 24/48xy•1/6xy | | 8/5a=6 | | 3(3x-5)=10 | | 5m+8=8m-4 | | 24x•1/2y•1/6xy | | -4x^4-3x^2+1=0 | | 6+11x-2=9x+16-4x | | 11=3s-4(27-s) | | -5x-2=15 | | x-0.3x=15.40 | | 1.5(12-3x)=12(1.5-3x) |